2007
DOI: 10.1557/jmr.2007.0098
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of montmorillonite clays with modulable porosity induced with acids and superacids

Abstract: The structural transformation of natural montmorillonite clay with different acids and superacids (hydrochloric, HCl; sulfuric, H 2 SO 4 ; hydrofluoric, HF; perchloric, HClO 4 ; chlorosulfonic, HSO 3 Cl; and trifluoromethanesulfonic, HSO 3 CF 3 acids) is evaluated by various techniques, allowing its full characterization. The process involves the modulated digestion of the aluminum and silicon atoms from the original clay without the loss of the original mass in the material from a careful drying methodology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 61 publications
0
3
0
1
Order By: Relevance
“…To investigate the novel catalytic capabilities of TAFF, this work studied the transformation of para -methoxybenzyl acetate ( 1 ). Despite the Lewis and Brønsted-Lowry acid character of the studied clay, its acidity is very low in comparison with sulfuric or triflic acids [19]. Thus, the phenylmethanes 2 - 4 and linear oligomers 5 - 8 were obtained when the reaction was carried out in carbon disulfide at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the novel catalytic capabilities of TAFF, this work studied the transformation of para -methoxybenzyl acetate ( 1 ). Despite the Lewis and Brønsted-Lowry acid character of the studied clay, its acidity is very low in comparison with sulfuric or triflic acids [19]. Thus, the phenylmethanes 2 - 4 and linear oligomers 5 - 8 were obtained when the reaction was carried out in carbon disulfide at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Adicionalmente se identificó silicato de aluminio. Después del tratamiento ácido y térmico, los picos característicos de la haloista permanecen prácticamente iguales, sin embargo los correspondientes al silicato de aluminio se ven incrementados, resultado que indica que en las condiciones del experimento, se extrae parte del alumnio y del silicio, pero se mantiene la estructura de la haloista, resultados similares se han obtenido con el tratamiento ácido (clorhídrico) y térmico de montmorillonita (Vargas-Rodríguez, Beltrán, Vázquez-Labastida, Linares-López, & Salmón, 2007).…”
Section: Caracterización Del Catalizadorunclassified
“…With respect to the first point, Weiss et al proposed that OH groups at the end of silicate layers, which were formed by aluminum extraction from octahedral sheets, are the sites of alkyl‐aluminum fixation on which the metallocene complexes are activated. Acid treatment of MMT induces morphological changes such as increased surface area (SA) and pore volume (PV) . Therefore, the position of the surface species proposed by Weiss et al would closely be related to the morphological changes of MMT.…”
Section: Introductionmentioning
confidence: 99%
“…Acid treatment of MMT induces morphological changes such as increased surface area (SA) and pore volume (PV). [4][5][6][7][8] Therefore, the position of the surface species proposed by Weiss et al [3] would closely be related to the morphological changes of MMT. In contrast, Kurokawa et al reported that metallocene complexes are intercalated into the layer, where ethylene polymerization proceeds when Mg 2+ cationexchanged mica is used.…”
Section: Introductionmentioning
confidence: 99%